Makna Konotatif dalam Lirik Lagu “Berisik” Karya Dere dan Tulus - Anggraini*, Eva Fitri; Marwan, Iwan (Universitas Suryakanca, 2024)
This article will describe the connotative meaning in the lyrics of the song